Feasibility Analysis of Gold Pawn Financing under Sharia-Based Good Corporate Governance: Evidence from Bank Syariah Indonesia - Athia Nur Kamilah; Muhammad Iqbal Surya Pratikto; Miftah Hur Rahman ZH (Cv. Kayaswara, Indonesia, 2025)
This study aims to analyze the feasibility assessment of gold pawn financing products and the implementation of Sharia-based Good Corporate Governance (GCG) at Bank Syariah Indonesia, KCP Surabaya Manukan. A descriptive qualitative approach was employed, with data collected through observation, interviews, and documentation. Data analysis involved reduction, presentation, and conclusion drawing. The findings reveal that the bank applies three feasibility indicators: character, capacity, and collateral (assessed through physical testing, chemical testing, and specific gravity testing), while capital and condition of economy are not applied. The implementation of Sharia-based GCG covers transparency, accountability in accordance with relevant laws and DSN-MUI fatwas, and fairness in customer service. However, accountability and professionalism aspects remain suboptimal due to the lack of specialized gold pawn training for staff, despite formal appointment. This condition may pose operational risks to the bank.